Analisis Pengalaman Pengguna (User Experience) pada Aplikasi Marketplace OLX menggunakan Usability Testing - Yusuf Habib Alfatha; Satrio Agung Wicaksono; Mochamad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
In Indonesia OLX is the largest platform for promoting online classified ads. This platform can be used by anyone for free by visiting the website and downloading the application. The OLX platform mobile app got several reviews from its users who found the system not what they expected. The location of the ad in the application makes them touch it often, the item they were looking for was not displayed to their expectations, and second-hand promotion that can't appear without explanation. Because of that evaluation of the OLX application is necessary. The method used is usability testing and giving the SUS questionnaire. Usability attributes that will be evaluated are learnability, memorability, efficiency, effectiveness, error, readability, and satisfaction. The effectiveness attribute scores 75% and 100% for the both group and did a little misstep for the error attribute. For efficiency attribute the average participant can complete a task by 3.3% in one second and for the learnability aspect, participants get 1.5x faster when compared to the first use of system. Then the memorability attribute has increased, the average number of steps is 114 to 58 steps. For the readability aspect, the average participant gets a score of 87 for understanding the application content. Then the satisfaction attributes measured using the SUS questionnaire produced a score of 67.9.